Representasi Perjuangan Perempun dalam Film Athirah Karya Alberhiene Endah (Pendekatan Feminisme) - Nurhikmah, Nurhikmah; Azis, Sitti Aida; Anzar, Anzar (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2024)
The movie business will not lika-liku will all go back to human life.Film with different types of behavior arose because the film audience, consumer and created to satisfy the appetite.Representation can be defined as a representative action, or situation representative called representation in Indonesian Language Dictionary Large (KBBI).The purpose of this research is to describe the women portrayed in a film athirah dengam adopting feminism.This study using the kind of research description by a qualitative approach.A technique used in this research is a technique roll and note. The data collection is done by means of watching his film and athrah iterative for obtaining understanding of any dialogue that is delivered in athirah film.Based on the results of the study shows women struggle in respects and responsibilities athirah in maintaining the unity of households that household remain harmonious.